STUDY OF TEENAGERS' ATTITUDES REGARDING THE RISK OF CHILD MARRIAGE AT AHMAD YANI 2 BAURENO HIGH SCHOOL, BOJONEGORO DISTRICT - sri mulyani; Musheer Aljaberi; Norhashima Binti Abd Rashid (Sahabat Publikasi Kuu, 2024)
A person's Attitude towards an object is a feeling of support or favor (favorable) or feelings of not supporting or not taking sides (unfavorable) on a particular object. The Attitude of teenagers who are not good is a factor in the occurrence of child marriage; they generally do not understand the risks to their bodies. The purpose of this study is to determine the attitudes of adolescents about the risk of child marriage. This research uses a descriptive method. The population is all teenagers at Ahmad Yani 2 Baureno High School, Bojonegoro Regency; in June 2022, there are as many as 226 teenagers. The sample in grades X and XI was taken by accidental sampling, so the number of samples was 125 people. Collect data using a questionnaire, then edit, code, score, and tabulate, which is then presented as a frequency table with percentages and narration. The results showed that more than half of the respondents, namely 66 children (52.8%), were favorable/positive (supportive) that child marriage could result in negative risks, and less than some of the respondents, namely 59 children (47.2%) were unfavorable/negative (does not support) that child marriage may result in negative risks. More than some teenagers have a favorable/positive attitude (support) that child marriage can lead to negative risks, it is hoped that the active role of health workers is to provide counseling to adolescents about child marriage. Especially adolescent girls about a good age for reproductive health and the impact that can be felt when doing child marriage